2010
DOI: 10.1007/s00784-010-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient satisfaction with complete dentures and oral health-related quality of life: two-year longitudinal assessment

Abstract: The objective was to evaluate the development of oral health-related quality of life (OHRQoL) in patients with complete dentures and the association between OHRQoL and patient satisfaction. Fifty-two patients (mean age, 66.3, 48.1% male) received dentures in at least one jaw. The analysis was conducted on participants with dentures in both jaws (CD-Both; n = 22) or in the upper jaw only (CD-Max; n = 28). Data were collected 4 weeks, 6 months, and 1 and 2 years after insertion. OHRQoL was measured by use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 22 publications
3
65
0
1
Order By: Relevance
“…Matthias et al 23 constataram que os idosos aceitavam a perda de dentes mais facilmente por considerarem que tais perdas são resultantes de um processo natural do envelhecimento. Além disso, verifica-se que alguns idosos, devido a repetidos problemas com seus dentes naturais, consideram haver uma real melhora da saúde bucal com a substituição dos mesmos por próte-ses parciais ou totais 6,18,30,40 .…”
Section: Discussionunclassified
“…Matthias et al 23 constataram que os idosos aceitavam a perda de dentes mais facilmente por considerarem que tais perdas são resultantes de um processo natural do envelhecimento. Além disso, verifica-se que alguns idosos, devido a repetidos problemas com seus dentes naturais, consideram haver uma real melhora da saúde bucal com a substituição dos mesmos por próte-ses parciais ou totais 6,18,30,40 .…”
Section: Discussionunclassified
“…The OHIP is a well-tested and standardized assessment instrument for measuring the OHRQoL. [21][22][23][24] It consists of 49 items that are grouped into 7 domains on the basis of a generic model of the disease and its consequences, which are derived from the international classification of impairments, disabilities, and handicaps. 25 Analogous to the original OHIP developed in Australia, 26 the OHIP consists of 49 original items, which are grouped into 7 subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Stober et al also concluded that patient satisfaction and OHRQoL were significantly associated with complete denture wearers, confirming the importance of prosthodontics treatment for edentulous patients [16].…”
Section: Int J App Pharm Vol 9 Special Issue 2 2017mentioning
confidence: 90%